The Burkholderia mallei BmaR3-BmaI3 Quorum-Sensing System Produces and Responds to N-3-Hydroxy-Octanoyl Homoserine Lactone - Duerkop, Breck A. (American Society for Microbiology (ASM), 2008)
Burkholderia mallei has two acyl-homoserine lactone (acyl-HSL) signal generator-receptor pairs and two additional signal receptors, all of which contribute to virulence. We show that B. mallei produces N-3-hydroxy-octanoyl HSL (3OHC(8)-HSL) but a bmaI3 mutant does not. Recombinant Escherichia coli expressing BmaI3 produces hydroxylated acyl-HSLs, with 3OHC(8)-HSL being the most abundant compound. In recombinant E. coli, BmaR3 responds to 3OHC(8)-HSL but not to other acyl-HSLs. These data indicate that the signal for BmaR3-BmaI3 quorum sensing is 3OHC(8)-HSL.